2008
DOI: 10.1021/ja801655d
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine Ring Opening at Room Temperature at a Rhenium Tricarbonyl Bipyridine Complex

Abstract: Pyridine ring opening occurs in the reaction of [Re(CO)3(MeIm)(bipy)]OTf with KN(SiMe3)2 followed by double methylation with methyl trifluoromethanesulfonate. Analogues of the neutral product of the initial deprotonation and of the product of the first methylation were isolated by using mesitylimidazole (MesIm) in place of methylimidazole (MeIm) and/or 1,10-phenanthroline (phen) instead of 2,2'-bipyridine (bipy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 25 publications
5
57
0
Order By: Relevance
“…The most informative features of the 1 H NMR spectrum of 3 are the signals between 4.36 and 6.00 ppm, corresponding to the hydrogen atoms of a dearomatized 2‐pyridyl ring. Similar shielded signals were found in the 1 H NMR spectra of previously characterized products of nucleophilic attack at one pyridyl ring 1. 12 In addition, the 1 H NMR spectrum of 3 includes two different P‐bonded methyl groups and two disastereotopic hydrogens on a P‐bonded methylene group.…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…The most informative features of the 1 H NMR spectrum of 3 are the signals between 4.36 and 6.00 ppm, corresponding to the hydrogen atoms of a dearomatized 2‐pyridyl ring. Similar shielded signals were found in the 1 H NMR spectra of previously characterized products of nucleophilic attack at one pyridyl ring 1. 12 In addition, the 1 H NMR spectrum of 3 includes two different P‐bonded methyl groups and two disastereotopic hydrogens on a P‐bonded methylene group.…”
Section: Methodssupporting
confidence: 67%
“…Interligand CC coupling initiated by deprotonation of appropriately positioned CH groups has been demonstrated in a few examples. Thus, N ‐alkylimidazoles have been coupled with bipy or phen (1,10‐phenanthroline),1 other N ‐alkylimidazoles,2 nitriles, isonitriles,3 CO,4 and monodentate pyridines 5. Similar couplings of monodentate pyridines, followed by oxidation, afforded bipyridines 5b.…”
Section: Methodsmentioning
confidence: 99%
“…[8] About at the same time, we found that the deprotonation reaction of the analogous rhenium compounds, [ReA C H T U N G T R E N N U N G (bipy)(CO) 3 A C H T U N G T R E N N U N G (N-RIm)]OTf (R = methyl, mesityl; OTf = triflate), led to a completely different kind of product. [9] As shown in Scheme 1b, the re-A C H T U N G T R E N N U N G action of the rhenium species with a strong base deprotonated the imidazole C2 À H group, and the so formed carbeniate attacked a C ortho of the adjacent 2,2'-bipyridine ligand. As a consequence, C À C coupling and loss of aromaticity of the involved ring were observed.…”
Section: -C 4 H 7 )A C H T U N G T R E N N U N G (Bipy)(co) 2 a C H Tmentioning
confidence: 99%
“…In the case of titanium, a titanium alkylidyne is a proposed intermediate. Recently, a few examples of aromatic N-heterocycle cleavage by late transition metal complexes have also been reported; these systems involve rhenium [15,16] and tungsten metal centers [17].…”
Section: Introductionmentioning
confidence: 99%